Novel method for measuring junctional proton permeation in isolated ventricular myocyte cell pairs. - Swietach, P; Vaughan-Jones, R (2004)
Partial exposure of single ventricular myocytes to membrane-permeant weak acids or bases, using a dual-microperfusion technique, generates large and stable intracellular pH (pHi) gradients. In this study, we have investigated the feasibility of using the technique to estimate junctional proton permeability. This was done by recording the pHi gradient developed across the junctional region of a pair of conjoined ventricular myocytes, isolated enzymically from a guinea pig heart when one of the cells was partially exposed to acetate or ammonium. We show that under HEPES-buffered conditions, the junctional discontinuity in the pHi profile can be used to derive an apparent proton permeability coefficient (PHapp). The mean PHapp obtained was 4.45 +/- 0.21.10(-4) cm/s (n=43) at an average junctional pHi of 7.04 +/- 0.02. In the presence of the junctional inhibitor alpha-glycyrrhetinic acid, exposure of the proximal cell to weak acid or base produced no pHi change in the distal cell, confirming that distal changes were normally caused by acid-base flux through connexons assembled into junctional channels. The validity of the dual-microperfusion method was tested further by using a diffusion-permeation-reaction model for intracellular protons, designed to highlight possible errors in the estimates of PHapp. Our technique for measuring PHapp provides a useful alternative to the previous, more invasive technique of locally loading acid through a cell-attached patch pipette. The technique may provide a simple method for investigating the factors regulating cell-to-cell proton transmission.